2019
DOI: 10.1089/tmj.2018.0058
|View full text |Cite
|
Sign up to set email alerts
|

Videoconferencing Psychotherapy and Depression: A Systematic Review

Abstract: VCP for the treatment of depression is a promising method for delivering mental health services. More rigorous research is needed to evaluate VCP on depression in various contexts and participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
177
0
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(206 citation statements)
references
References 51 publications
(63 reference statements)
11
177
0
18
Order By: Relevance
“…The World Health Organisation defines telemedicine as "the delivery of health care services, where distance is a critical factor, by all health care professionals using information and communication technologies for the exchange of valid information for diagnosis, treatment and prevention of disease and injuries, research and evaluation, and for the continuing education of health care providers, all in the interests of advancing the health of individuals and their communities" [20]. Previous work has demonstrated the feasibility of using telemedicine to assist with the clinical care of patients with a wide spectrum of neurological conditions including stroke [16,21,22], headache [23][24][25], multiple sclerosis [26], mental health disorders [27,28], epilepsy [29,30] and neurodegenerative diseases [31][32][33][34]. Although preliminary studies have suggested that telemedicine may be helpful in providing sideline and inoffice care to patients with concussion [35,36], there have been no studies that have examined the use of this technology to provide clinical care of paediatric concussion patients living in remote and medically underserviced communities in northern Canada.…”
mentioning
confidence: 99%
“…The World Health Organisation defines telemedicine as "the delivery of health care services, where distance is a critical factor, by all health care professionals using information and communication technologies for the exchange of valid information for diagnosis, treatment and prevention of disease and injuries, research and evaluation, and for the continuing education of health care providers, all in the interests of advancing the health of individuals and their communities" [20]. Previous work has demonstrated the feasibility of using telemedicine to assist with the clinical care of patients with a wide spectrum of neurological conditions including stroke [16,21,22], headache [23][24][25], multiple sclerosis [26], mental health disorders [27,28], epilepsy [29,30] and neurodegenerative diseases [31][32][33][34]. Although preliminary studies have suggested that telemedicine may be helpful in providing sideline and inoffice care to patients with concussion [35,36], there have been no studies that have examined the use of this technology to provide clinical care of paediatric concussion patients living in remote and medically underserviced communities in northern Canada.…”
mentioning
confidence: 99%
“…The themes and sub-themes produced by co-researchers are largely reflective of the wider literature in the field [52]. This is encouraging given that the panel were inexperienced and unfamiliar with the evidence regarding digital mental health services.…”
Section: Researcher Reflections On Co-researcher Analysismentioning
confidence: 70%
“…The authors also mentioned a lack of studies concerning the treatment of generalized anxiety disorder [59]. With regard to the treatment of depression, a systematic review by Berryhill and colleagues [17] showed that videoconferencing was also a valuable treatment option. Out of the 33 studies included in the systematic review, 21 studies reported statistically significant reductions in depressive symptoms after videoconferencing therapy.…”
Section: Chat / E-mail / Videoconferencementioning
confidence: 99%